The handbook of service industries (Edward Elgar, 2007)
Service activities are now acknowledged as key players in economic development, societal change and public policy worldwide. This exciting new Handbook not only contributes to ongoing conceptual debates about the nature of service-led economies and societies; it also pushes back the frontiers of current critical thinking about the role of service activities in urban and regional development and the important research agendas that remain to be addressed. Drawing on both theory and case studies, the contributors are international experts who have written original and stimulating chapters from a number of different disciplinary perspectives. Each chapter seeks to raise awareness of, and to provoke debates about, the opportunities and challenges presented by the shift to service employment.